Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.24996/ijs.2020.si.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Supra Rough Membership Relations and Supra Fuzzy Digraphs on Related Topologies

Abstract: The primary aim of this paper is to present two various standpoints to define generalized membership relations, and state the implication between them, in order to categorize the digraphs and assist for their gauge exactness and roughness. In addition, we define several kinds of fuzzy digraphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Kanstrup and Thomas 93 indicated that such a transition across the EU could be implemented within 3-4 years of passage of an EU regulation applied to wetland hunting. The introduction of a comprehensive regulation restricting the importation, sale, carrying and use of lead ammunition for all hunting would substantially facilitate monitoring, enforcement and compliance and seen, for example, in Denmark after the total ban of use, sale and possession of lead gunshot 94 . The burden of responsibility would include importers and retailers and this is far easier and more cost effective to monitor and enforce than partial bans where activities need to be monitored at the level of the individual hunter.…”
Section: Eu Regulatory Measuresmentioning
confidence: 99%
“…Kanstrup and Thomas 93 indicated that such a transition across the EU could be implemented within 3-4 years of passage of an EU regulation applied to wetland hunting. The introduction of a comprehensive regulation restricting the importation, sale, carrying and use of lead ammunition for all hunting would substantially facilitate monitoring, enforcement and compliance and seen, for example, in Denmark after the total ban of use, sale and possession of lead gunshot 94 . The burden of responsibility would include importers and retailers and this is far easier and more cost effective to monitor and enforce than partial bans where activities need to be monitored at the level of the individual hunter.…”
Section: Eu Regulatory Measuresmentioning
confidence: 99%
“…102 TFEU followed by the CJEU since Intel, 101 in MEO, the Court added that the competition enforcer should take into consideration "all the relevant circumstances" in order to determine whether price discrimination may produce a competitive disadvantage that distorts competition in the downstream market. 102 By analogy with Intel, the CJEU ruled that the competition agency should take the following elements into consideration in its analysis: 103 -the negotiating power of the customer of the dominant firm as regards the tariffs.…”
Section: Iiia2 Competitive Disadvantagementioning
confidence: 99%
“…As the applications have been increasingly appearing in multiple aspects in mathematics, there has been a growing interest in this concept [13,14]. Our research topic has further relations with additional previous works [15,16]. In this paper, we introduce the concept of cutpoints, with the topological viewpoint in -connected topological spaces, and study separations and connectedness in the -topological spaces.…”
Section: -Introductionmentioning
confidence: 97%